2012
DOI: 10.3126/kumj.v9i1.6258
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Ventilator-Associated Pneumonia in Kathmandu University Hospital

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
3
16
0
Order By: Relevance
“…was the most common causative agent of VAP. Regarding gender of the patients there was no significant difference between VAP and non VAP groups which was similar to the findings by Ranjit and Bhattarai (14) in their study, where older age was significantly associated with increased risk of VAP. That is in agreement with another study by Giard et al, (15) which revealed that, advanced age was independent risk factors for LVAP acquired in ICU.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…was the most common causative agent of VAP. Regarding gender of the patients there was no significant difference between VAP and non VAP groups which was similar to the findings by Ranjit and Bhattarai (14) in their study, where older age was significantly associated with increased risk of VAP. That is in agreement with another study by Giard et al, (15) which revealed that, advanced age was independent risk factors for LVAP acquired in ICU.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the result by Saravu et al, (16) but in contrast to Ranjit and Bhattarai study. (14) H 2 blockers usage can alter the gastric pH thereby facilitating organism multiplication which, when aspirated, can lead to occurrence of VAP. Prior antibiotic usage was higher among the cases, but the association was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Higher incidence of VAP occurred in poisoning, post laparotomy and COPD in a study by Ranjit et al [20] . In a a study by Mohanty et al, the maximum number of cases were Cerebrovascular accident and sepsis [21] .…”
Section: Distribution Of Vap Cases By Diagnosismentioning
confidence: 85%
“…The hospital stay was 18.56 ± 13.83 days in monomicrobial VAP and 21 ± 9.7 days in polymicrobial VAP. In a study by Ranjit et al,the VAP patients had longer duration of mechanical ventilation (18.88±7.7 days ) and stay (29±17.8 days ) [20] A study by Mohanty et al, also reported longer duration of mechanical ventilation and hospital stay in VAP patients [21] .…”
Section: Multi Drug Resistance In Vap Isolatesmentioning
confidence: 93%
“…The full texts of 69 potentially eligible studies were then strictl y assessed. Sixteen studies [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were included in the systematic review. Finally, 12 studies [23][24][25][26][27][28][29][30][31][32][33][34] were included in the present meta-analysis (…”
Section: Literature Selectionmentioning
confidence: 99%